The Impact of Organizational Innovation Capability, Organizational Agility, and Digital Strategy on Business Resilience in Food and Beverage SMES: The Mediating Role of Adaptability and the Moderating Role of Transformational Leadership - Umi Suryani; Irsyad Parama Dwiputra (Indonesian Interdisciplinary Journal of Sharia Economics)
This study explores the influence of innovation capability, organizational agility, and digital strategy on business resilience in food and beverage (F&B) SMEs, focusing on the mediating role of organizational adaptability and the moderating role of transformational leadership. Conducted in Malang City, Indonesia, the research involves 100 SME owners and managers selected using purposive sampling. Data were collected through structured questionnaires and analyzed SEM-PLS. The findings indicate that organizational agility and digital strategy significantly impact business resilience directly, while innovation capability affects resilience indirectly through organizational adaptability. Organizational adaptability emerges as the strongest predictor of resilience, emphasizing its critical role in enabling SMEs to respond effectively to market dynamics. Although transformational leadership was not a statistically significant moderator, it shows the potential to foster adaptability and integrate innovation. The study concludes that SMEs should prioritize enhancing adaptability through strategic flexibility, continuous learning, and collaboration. Leveraging digital tools and fostering agility are also essential for building resilience. Policymakers are advised to support SMEs by addressing digital transformation challenges, such as resource limitations and low digital literacy. Additionally, investment in leadership development and adaptable innovation strategies can further strengthen SME resilience. This research contributes to academic literature and provides practical insights for F&B SMEs in navigating uncertainty, ensuring sustainability, and improving competitiveness in a dynamic market environment.